Stymulowanie przez nauczycieli aktywności samokształceniowej uczniów klas 1–3 szkoły podstawowej – raport z badań - Flanz, Jolanta (Kultura-Społeczeństwo-Edukacja, 2021)
The necessity of developing students’ competences concerning independent learning is easily noticeable in both Polish and international educational documents as well as in scientific literature. This article contains an attempted answer to a question in what way teachers stimulate independent learning activities of primary school students (grade 1 to grade 3). This was the aim of the research conducted with the help of selected group of teachers from Kuyavian-Pomeranian Voivodeship in Poland. The research checked for instance how the teachers encourage the students to independent learning, how they are formulating their homework tasks, and whether they apply the multi-level learning approach. The results of this study are presented in this report.